Hubungan antara Komunikasi Keluarga dengan Pembentukan Karakter Islami Anak - Alifya Syahrani; Yenni Yuniati (UNISBA Press, 2024)
Abstract. Family communication is an interaction between parents and children which aims to form affection, cooperation and trust in a relationship. The formation of ideal family communication, of course, also requires the formation of good children's character, depending on how parents educate their children. This research has the aim of family communication indicators, namely to determine and analyze the relationship between openness, empathy, supportive attitudes, equality, positive attitudes of parents and children's character. By using interpersonal communication theory, namely the interaction of two people who communicate verbally and non-verbally at the same time with the speed of receiving feedback. This research uses quantitative research methods, with correlational studies because researchers want to know how big the relationship is between family communication and the formation of children's character. The population chosen by researchers was 150 parents who had children aged 14-20 years, and obtained a sample of 60 people. The research results show a relationship between family communication and the formation of children's character with a correlation coefficient of 74% with a significance of 0.000 <0.01. The relationship between the two variables X and variable Y is included in the category of a very strong relationship. And the formation of children's character is more dominant in the variables of supportive attitudes and positive attitudes with Islamic values, namely tasamuh and husnudzon. Abstrak. Komunikasi keluarga merupakan interaksi antara orang tua dan anak yang bertujuan untuk membentuk kasih sayang, kerjasama, dan kepercayaan dalam suatu hubungan. Terbentuknya komunikasi keluarga yang ideal, tentunya perlu terbentuk juga karakter anak yang baik, tergantung pada cara mendidik orang tua kepada anak. Penelitian ini memiliki tujuan dari indikator komunikasi keluarga yaitu untuk mengetahui dan menganalisis hubungan antara keterbukaan, empati, sikap mendukung, kesetaraan, sikap positif orang tua dengan karakter anak. Dengan menggunakan teori komunikasi interpersonal yaitu interaksi dua orang yang berkomunikasi verbal dan nonverbal sekaligus dengan memiliki kecepatan penerimaan umpan balik. Penelitian ini menggunakan metode penelitian kuantitatif, dengan studi korelasional karena peneliti ingin mengetahui seberapa besar hubungan antara komunikasi keluarga dengan pembentukan karakter anak. Populasi yang dipilih peneliti sebanyak 150 orang tua yang memiliki anak usia 14-20 tahun, dan memperoleh sampel sebanyak 60 orang. Hasil penelitian terdapat hubungan antara komunikasi keluarga dengan pembentukan karakter anak dengan nilai korelasi koefisien sebesar 74% dengan signifikansi 0,000 < 0,01. Hubungan antara kedua variable X dan variable Y termasuk kedalam kategori hubungan yang sangat kuat. Serta pembentukan karakter anak lebih dominan pada variabel sikap mendukung dan sikap positif dengan nilai keislaman yaitu tasamuh dan husnudzon.